Aspiration versus stent retriever for posterior circulation stroke: A meta‐analysis. (13th December 2022) - Guo, Xiumei; Xiong, Yu; Huang, Xinyue; Pan, Zhigang; Kang, Xiaodong; Chen, Chunhui; Zhou, Jianfeng; Wang, Cui'e; Lin, Shu; Hu, Weipeng; Wang, Lingxing; Zheng, Feng
Abstract: Aims: New thrombectomy strategies have emerged recently. Differences between posterior circulation stroke management via aspiration and stent retriever remain to be evaluated. We compared the safety and efficacy of aspiration and stent retriever in treating posterior circulation stroke. Methods: Three databases (PubMed, Embase, and Cochrane Library) were systematically searched for studies comparing aspiration and stent retriever in patients with posterior circulation stroke. The modified Newcastle‐Ottawa scale was used to assess the risk of bias. A random‐effects model was used. Results: Fifteen cohort studies with 1451 patients were included. Pooled results showed a significant difference in total complication (odds ratio [OR] 0.48, 95% confidence interval [CI] [0.30, 0.76], p  = 0.002). successful recanalization (1.85, [1.30, 2.64], p  = 0.0006), favorable outcome (1.30, [1.02, 1.67], p  = 0.04), procedure duration (−22.10, [−43.32, −0.88], p  = 0.04), complete recanalization (4.96, [1.06, 23.16], p  = 0.009), and first‐pass effect (2.59, [1.55, 4.32], p  = 0.0003) between the aspiration and stent retriever groups, and in favor of aspiration. There was no significant difference in the outcomes of rescue therapy (1.42, [0.66, 3.05], p  = 0.37) between the two groups. Conclusion: Patients with posterior circulation stroke receiving treatment with aspiration achieved better recanalization, first‐pass effect, and shorter procedure time. Aspiration may be more secure than a stent retriever. Abstract : Patients with posterior circulation stroke receiving treatment with aspiration than that with a stent retriever achieved better recanalization, first‐pass effect, and shorter procedure time. Aspiration may be more secure than a stent retriever.